O Chile de Lagos: o desafio de um novo curso democrático - Aggio, Alberto [UNESP] (Universidade Estadual Paulista (Unesp), 2000)
O texto analisa sinteticamente o processo de transição à democracia no Chile e observa de que forma os elementos centrais desse processo apareceram no recente processo eleitoral vivido por aquele país. Por meio desse enfoque, analisa as condições que estiveram presentes na primeira eleição presidencial em dois turnos que se realizou no Chile, bem como as características e limites das duas principais candidaturas: Ricardo Lagos e Joaquín Lavín.

The text analyses synthetically the transition process towards democracy in Chile and observes how the central elements of this process appeared in the Chilean recent elections. Through this approach, it also analyses the conditions present in the first presidential election in two phases realized in Chile as well as the characteristics and limits of the two main candidatures: Ricardo Lagos and Joaquín Lavín.
The Chile of Lagos: the challenge of a new democratic path
Keywords: Chile; Democracy; Left; Right; Political Party; Democracia; Esquerda; Direita; Partidos